Comparative Pharmacological Evaluation of Aloe vera and Urena lobata Extracts Against Indomethacin-Induced Gastric Ulceration in Rodent Models - Agrahari, Vishal Kumar; Sirohi, Brajesh; Gupta, Naveen; Rajput, Dharmendra Singh; Patel, Ganesh Prasad; Kaushal, Brajmohan (Journal of Neonatal Surgery, 2025)
Recent advancements in Public Health Systems, diagnostic modalities, and therapeutic agents have not markedly ameliorated the impacts of peptic ulcer disease (PUD). Although there have been optimization shifts in the management of ulcer disorders owing to the incorporation of formulated artefactual medications such as proton pump inhibitors, H₂ receptor antagonists, prostaglandin analogues, and the protective antimicrobials aimed against Helicobacter pylori, the repurposed medications have all been associated with adverse events, withdrawal, and reoccurrence of ulceration, and there are rising concerns of antimicrobial resistance to antiseptic agents, further underlying the urgent need to consider and investigate the incorporation of non-artificial medicine. The protective properties of medicinal plants drafted as gastroprotective agents and ulcer neuralizers have been characteristically in use in a variety of ancient ethnomedical practices and are now gaining renewed interest. Aloe vera (Asphodelaceae) and Urena lobata (Malvaceae) have been documented in ethnomedical literature for a range of properties, including but not limited to, gastroenteric illnesses, repair of damaged tissues, and the management of inflammatory disorders; however, there are observations of scanty literature comparing the therapeutic potential of Aloe vera and Urena lobata in the clinical and therapeutic management of ulceration.This study provides extensive insight into the comparative study of Aloe vera and Urena lobata using experimentally induced stomach ulcer models in Wistar rats. Distilled water and ethanol extracts of the two plants were prepared, standardized and subjected to various pharmacological and spectral characterizations (UV–Vis, FTIR, ¹H-NMR) to determine their metabolic profiling. Compliance with the OECD 425 guidelines confirmed the absence of any toxic effects and a good safety margin up to 2000 mg/kg for the study. The study of the antiulcer activities were determined using three well known rodent models: indomethacin-induced mucosal injury (prostaglandin-inhibition model), ethanol induced acute necrotizing ulceration (oxidative stress model), and pylorus ligation model (acid–pepsin hypersecretion model). Various ulcer evaluation techniques were used to provide a comprehensive evaluation strategy: ulcer index, analysis of gastric secretions, mucus quantification, assessment of the antioxidant markers SOD, CAT, GSH, MDA, profiling of pro- and anti-inflammatory cytokines (such as TNF-α, IL-1β, IL-10, TGF-β), and careful histopathological evaluation. Aloe vera provided pronounced cell protective effects in the development of stomach ulcers by modifying gastric secretion, restoration of oxidative homeostasis, and by improving the ulcer protective mucus barrier. In contrast, Urena lobata also provided some protection of the gastro tract and moderate protection of gastric ulcers, but also provided a remarkable healing and restoration in the chronic stages of ulcers by enhancing the proliferation of fibroblasts, collagen synthesis, TGF-β secretion, and ultimately tissue remodelling and mucosal improvement. The findings were corroborated and explained at the microscopic level: Aloe vera diminished epithelial degradation and inflammatory infiltration; Urena lobata restored the architecture of the stomach by stimulating orderly collagen deposition and re-epithelialization. The mechanistic differences highlight the distinct pharmacodynamics of Aloe vera as a fast-acting antioxidant and anti-inflammatory, and Urena lobata as a highly effective mucosal healing and regenerative agent. This is primarily the reason why both plants have been historically used and justifies the potential use of these plants in developing pharmaceutical combinations as a safer alternative to synthetic anti-ulcer medications